2005
DOI: 10.1210/en.2004-0735
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Causes Bone Loss in Mice by Suppressing Osteoblast Differentiation and Bone Formation

Abstract: Because osteoblasts and marrow adipocytes are derived from a common mesenchymal progenitor, increased adipogenesis may occur at the expense of osteoblasts, leading to bone loss. Our previous in vitro studies indicated that activation of the proadipogenic transcription factor peroxisome proliferator-activated receptor isoform gamma 2 with rosiglitazone suppressed osteoblast differentiation. Here, we show that 5-month-old Swiss-Webster mice receiving rosiglitazone for 28 d exhibited bone loss associated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
305
0
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 425 publications
(338 citation statements)
references
References 54 publications
18
305
0
15
Order By: Relevance
“…As mentioned earlier, osteoblast apoptosis increases with advancing age in mice [32]. Osteoblastogenesis also declines with age, perhaps due to diversion of the common progenitor toward the adipocyte lineage [23,125]. We have obtained preliminary evidence that the tonic suppression of bone formation by PPARγ increases with advancing age in mice as indicated by increased expression of Alox15 and PPARγ, as well as increased levels of oxidized lipid ligands of PPARγ [126].…”
Section: The Therapeutic Efficacy Of Intermittent Pth On the Osteopormentioning
confidence: 76%
See 1 more Smart Citation
“…As mentioned earlier, osteoblast apoptosis increases with advancing age in mice [32]. Osteoblastogenesis also declines with age, perhaps due to diversion of the common progenitor toward the adipocyte lineage [23,125]. We have obtained preliminary evidence that the tonic suppression of bone formation by PPARγ increases with advancing age in mice as indicated by increased expression of Alox15 and PPARγ, as well as increased levels of oxidized lipid ligands of PPARγ [126].…”
Section: The Therapeutic Efficacy Of Intermittent Pth On the Osteopormentioning
confidence: 76%
“…Thus, PPARγ exerts a tonic suppressive effect on osteoblast differentiation and bone formation, most probably by diverting uncommitted progenitors into the adipocyte lineage at the expense of the osteoblast lineage. In support of this contention, mice given the PPARγ ligand rosiglitazone exhibited increased marrow adipogenesis and decreased osteoblastogenesis associated with decreased bone formation and bone loss [23].…”
Section: Birth and Death As Determinants Of Osteoblast Numbermentioning
confidence: 91%
“…For example, we have not yet tested if Vanin-1, as in other cells, 53 suppresses the expression and function in BMSCs and MSCs, of peroxisome proliferator-activated receptor ␥, a promoter of adipogenesis but suppressor of osteochondral differentiation in mesenchymal precursor cells. 54 We have not directly examined long-term effects of Vanin-1 gene knockout on phenotype and ank/ank mortality. 2 Last, because artery calcification is mild and is detected later than skeletal abnormalities in ank/ank mice, 13 we did not evaluate the effects of Vanin-1 deficiency on artery calcification in situ in ank/ank mice.…”
Section: (K Johnson Et Al Unpublished Observations)mentioning
confidence: 99%
“…Recent evidence has emerged that the widely used thiazolidinediones, oral hypoglycaemic agents known as insulin sensitisers that are often prescribed when other medications have failed to reduce blood glucose levels in patients with type 2 diabetes, may have a negative effect on the skeleton and increase the risk of fracture [2]. Since 2004, preclinical [3][4][5][6][7] and clinical studies [8][9][10] have indicated that thiazolidinediones use could alter bone metabolism, resulting in reduced osteoblastic bone formation and accelerated bone loss. As suggested by recent evidence from an epidemiological study [9] and a clinical trial [11], thiazolidinediones use is associated with a decrease in bone density in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%